Pelatihan Pengelolaan Media Sosial sebagai Media Pemasaran pada SMK Pawyatan 3 Daha Kediri - Ayunaning, Kholidia; Makhrudy, Khoirul Aman; Prafitasiwi, Avisha Gita; Sutrisno, Rahmat Dwi; Arisandi, Tio; Muhammad, Syahnju Nuril (Jurnal Pengabdian Masyarakat dan Lingkungan (JPML), 2025)
The development of the use of social media is an opportunity that needs to be utilized well, so that it can be used as a marketing technique that can increase the acceptance of prospective new students. In the current digital era, e-marketing techniques are one of the marketing techniques that are taken into account. Social media, which is an application that is widely used by many people and can be easily accessed at any time, is one of the fastest ways to disseminate information. Prospective students and parents of prospective students can easily get information. Pawyatan 3 Vocational School Daha Kediri seizes the opportunities that exist. However, SMK Pawyatan 3 Daha Kediri has difficulty marketing using social media. For this reason, social media management training is needed so that it can be used as marketing media. So that Pawyatan 3 Daha Kediri Vocational School is able to make good use of social media and can expand the scope of marketing and increase prospective students.